The Impact of Social Media Sites on Students’ Behavior During the COVID-19 Pandemic “A Sociological Field Study at Tishreen University” - أحمد دارين; ميرنا دلالة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The COVID-19 pandemic has had a profound impact on various aspects of human life, including work, health, and social interactions. Widespread lockdown measures and stay-at-home orders have left many individuals feeling isolated and unable to participate in daily social activities. University students, in particular, have turned to social media platforms as a way to mitigate the effects of these restrictions. This study aims to examine how students’ use of social media sites affects their social behaviors during the pandemic. A questionnaire was distributed to a sample of Tishreen University students, which included personal information and inquiries about the use of social media and its impact on social behavior across four main axes. Statistical analysis revealed a positive relationship between the use of social media and improved communication between users. However, a negative relationship was found between social media use and the provision of psychosocial support, as well as its impact on real-life social relationships. Interestingly, there was no direct link between social media use and increased social awareness. Based on these findings, recommendations include implementing educational programs on responsible use of social media and providing psychosocial support to help students overcome potential negative influences. It also suggests encouraging the positive use of social media to enhance social relationships and awareness.